Improving Learning Outcomes of Basic Movement Patterns of the Game of Volleyball Through a Playing Approach for Class V Students at SDN Alue Keujrun - Sarniyus (Marga: Journal Of Innovation and Creatifity, 2023)
The general objective of this research is to improve student outcomes through the implementation of Basic Movement Patterns Learning in Volleyball Games using a play-based approach. Additionally, this study aims to obtain in-depth information about the application of game variations in the basic movement patterns of volleyball. The research design employed is Classroom Action Research (CAR). The subjects in this study are 12 students from class V at SDN Alue Keujrun. The research was conducted over two meetings spanning two cycles. Each cycle consisted of four stages. The first cycle indicated that through action, students can self-motivate. From this first cycle, the result was 8%, indicating it was incomplete. The second cycle, as a reflection of the first cycle, also demonstrated that action improves student learning outcomes. The result of the second cycle was 83%, indicating completion. Based on the findings of this research, it can be concluded that: (1) Learning basic movement patterns in volleyball games using a play-based approach enhances student learning outcomes, (2) Learning basic movement patterns in volleyball games using a play-based approach motivates students and encourages active participation in the learning process.